Speech by the Hon’ble Chief Minister, Penang, at the UMNO Bahagian Tanjung 19th National Day Anniversary Dinner to be held at the E&O Hotel on Moday, 27th September 1976 at 8.00 p.m. - Lim, Chong Eu (1976)
I would like to thank the Chairman and Members of the UMNO Bahagian Tanjung for having kindly invited my wife and I to your dinner to celebrate the 19th National Day Anniversary.